O território e as resistências do povo indígena Jenipapo-Kanindé: um estudo sobre sua cultura alimentar - Santos, Carolinne Melo dos (2023)
The present research dissects the territory of the Jenipapo-Kanindé ethnic group with emphasis on their food culture, where the experiences of agriculture, medicinal gardens, hunting and fishing in the village and the dishes produced from them were analyzed. In addition to the practices that still remain appropriate to the current reality of the families, even after a social rise acquired with the public policies of assistance to indigenous peoples such as health clinics and schools, discussions will also be part of their relations with the territory and indigenous spirituality from the songs of the toré ancestral ritual. The development of the research is qualitative, bibliographic, ethnographic with participant observation and semi-structured interviews. To this end, the theoretical basis covered the concepts of territory, indigenous land, food culture, indigenous movement, social cartography and audiovisual materials about the Jenipapo-Kanindé people. From the data collected in the field, a workshop with methodological bases of social cartography was developed with the community for the construction of a map of the food culture of the village where the planting areas, the residence of the farmers and the masters of food culture who hold the knowledge of traditional dishes, hunters and fishermen were referenced. Through the interdisciplinary research together with the participation of the Jenipapo-Kanindé indigenous people we obtained social maps that presented the territory of the Encantada village based on their eating habits, thus identifying the food culture of this group.